Value of computerized inhibitory control test and blood tests in minimal hepatic encephalopathy diagnosis - Savlan, Ilona; Liakina, Valentina; Valantinas, Jonas (Acta medica Lituanica, 2013)
Background. Minimal hepatic encephalopathy (MHE) can be diagnosed by “paper-pencil” tests, computerised inhibitory control or critical flicker frequency tests, but for clinical practice more convenient methods of diagnosis are being searched. The aim of the study was to assess the value of inhibitory control test (ICT) and laboratory blood tests (leucocytes, platelets, hemoglobin, AST, ALT, ALP, GGT, bilirubin, albumin, SPA, INR, glucose, ammonia, IL-6) for MHE diagnosis. Materials and methods. 62 cirrhotic patients without overt hepatic encephalopathy were enrolled in the study. The control group consisted of 53 volunteers without chronic liver diseases. Routine laboratory tests, IL-6 of venous blood samples and ammonia of the capillary blood were extracted after overnight fasting. Ammonia was measured by the micro-diffusion method. IL-6 concentration was detected using the solid phase chemiluminescence immunometer analysis. At the same day all participants performed the PHES (Psychometric Hepatic Encephalopathy Score) battery and ICT under recommended diagnostic standards. Results. MHE was diagnosed in 44/71.0% out of 62 cirrhotic patients while 18/29.0% had no evidence of psychomotor or cognitive disturbances. There was not statistically significant difference in age, gender, education. Patients with MHE had statistically significant differences neither in leukocytes, platelets count nor in ALT, AST, ALP, GGT, IL-6, albumin, SPA, INR, bilirubin concentration in comparison with those without MHE. Patients with MHE perform ICT worse than those without MHE but the differences were not statistically significant. Conclusions. In our study ICT was not approved as a good diagnostic tool for MHE. The IL-6 concentration in the peripheral blood as well as routine biochemical tests seem not useful for MHE diagnosis in cirrhotic patients.
Keywords: minimal hepatic encephalopathy; IL-6; inhibitory control test; cirrhosis